Annual review on credit and financial issues: RDP and RCP - Kellogg, Clifton G.; Carpenter, Janney Bretz (South Shore Bank, 2016)
1. Overview of RDP and RCP financial performance 2. Credit and portfolio management 3. Branch-wise profitability 4. Long term financial projections for RCP